Оцінка залишкової міцності криволінійної ділянки трубопроводу зі статистично заданим корозійним дефектом, що розвивається у часі - Ларін, Олексій Олександрович; Потопальська, Ксенія Євгенівна (Луцький національний технічний університет, 2017)
В даній роботі проводилося дослідження з оцінки впливу корозійного об’ємного дефекту на працездатність коліна трубопроводу. Розвиток дефекту моделюється у часі. Оцінка характеристик напружено-деформованого стану конструкції з пошкодженням проводилась в рамках засобів комп’ютерного моделювання з використанням методу скінченних елементів. Визначено зони, в яких є локалізація максимальних напружень в пошкодженій ділянці трубопроводу з урахуванням стохастичного характеру розвитку корозійного пошкодження та наведена оцінка його впливу на залишкову міцність конструкції в період експлуатації від 35 до 45 років.

Pipelines are used as one of the most practical and low cost methods for transmission of different liquid petroleum products and gases. Damage on the pipeline is capable to appears during operation due to the accumulation of fatigue and arising of corrosion. In this paper, the assess of effect of a corrosion volumetric defect which is developing over time on the working capacity of the pipeline elbow has been carried out. The estimation of the characteristics of the stress-strain state of a design with damage is carried out with the framework of computer simulation using the finite element method (FEM). Corrosion damage models explicitly as volumetric defect on the out surface of the pipeline elbow. The zones on the damaged section of the pipeline on which the maximum stresses are localized has been defined, taking into account the stochastic nature of the development of corrosion damage. On the basis of the obtained results, the probabilistic characteristics of the stress strain state has been determined, such as mean value, coefficients of variation and asymmetry On the basis of these data, probability densities function of plasticity appearance have been obtained for different design time in operation at appropriate loading levels.
An estimation of residual strength of curvelinear pipeline part based on a statistical corrosion defect which is developing over a time
Keywords: корозійне пошкодження; магістральні трубопроводи; надійність; напружено-деформований стан; метод скінченних елементів; corrosion damage; pipeline; reliability